Water temperature alters predation risk and the adaptive landscape of induced defenses in plankton communities. (7th September 2015) - Riessen, Howard P.
Abstract: Water temperature influences many biological processes in zooplankton, including those that affect interactions with predators. These relationships help shape the impact of predation and the development of prey defenses. Many freshwater zooplankton develop induced morphological defenses in response to the presence of various invertebrate predators, a phenomenon that often has a seasonal pattern (cyclomorphosis) in which defenses are enhanced during summer when temperatures are highest. Here, I examine this relationship of water temperature to predation risk and the development of induced defenses by developing a life history model for the common pond‐dwelling water flea, Daphnia pulex and its response to predation by larvae of the phantom midge, Chaoborus, which involves the induction of defensive neck spines in the presence of predator kairomones. The model analyzes the influence of water temperature on Daphnia instar development time and body size, and on the encounter rate between Daphnia and Chaoborus, all of which affect the vulnerability of Daphnia to this gape‐limited ambush predator. It then assesses the costs and benefits of neck spine development, and thus its fitness consequences, in different temperature environments. Higher water temperatures increase predation risk for Daphnia, resulting in greater fitness advantages in producing induced defenses, but only at relatively high predator densities. This effect is greater at higher levels of food resources for the prey. These results demonstrate the importance of water temperature in influencing predation in plankton communities and help explain the phenomenon of cyclomorphosis in zooplankton, in which induced morphological defenses are limited to summer.